(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Not long ago, cybercrime became a reality. Such crimes are aimed at either jeopardising theimmense technological importance of data or exploiting it to perpetrate crimes that are not unliketraditional crimes, but are done in the cyberspace. As a result, contemporary societies are at danger ofsuffering significant losses. Cybercrime is carried out in the shadows, with no need for documentationor personal information. It is sent globally, bypassing borders and checkpoints. Furthermore, they areoften carried out by astute, technically adept criminals who are capable of removing evidence beforemoving on to the next target. All of these things make it simpler to perpetrate such crimes. Countriesthroughout the globe are facing significant hurdles in executing their criminal laws when it comes tocybercrime. The purpose of this research is to explore and evaluate the issue of cybercrime jurisdiction,cybercriminal extradition legislation, international agreements, and associated judicial laws.